2024
DOI: 10.1037/aca0000420
|View full text |Cite
|
Sign up to set email alerts
|

What are the benefits of mind wandering to creativity?

Abstract: A primary aim of mind-wandering research has been to understand its influence on task performance. While this research has typically highlighted the costs of mind wandering, a handful of studies have suggested that mind wandering may be beneficial in certain situations.Perhaps the most-touted benefit is that mind wandering during a creative-incubation interval facilitates creative thinking. This finding has played a critical role in the development of accounts of the adaptive value of mind wandering and its fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 45 publications
3
20
0
Order By: Relevance
“…1For related research on the association between task-unrelated thoughts and creativity, see Baird et al (2012), Smeekens and Kane (2016), and Murray et al (2021).…”
mentioning
confidence: 99%
“…1For related research on the association between task-unrelated thoughts and creativity, see Baird et al (2012), Smeekens and Kane (2016), and Murray et al (2021).…”
mentioning
confidence: 99%
“…Some authors, for example, suggested that MW might support adaptive functions such as planning, creative thinking, problem-solving, creative incubation, allowing dishabituation, and relieving tedium (Baird et al, 2012;Baird et al, 2011;Mooneyham & Schooler, 2013;Ruby et al, 2013;Stawarczyk et al, 2011). However, several studies failed to replicate a relation between problem-solving/creativity and mind wandering (Smeekens & Kane, 2016;Steindorf et al, 2021), particularly when considering MW contents and using probes instead of retrospective reports (Murray et al, 2021). Further, eventual benefits brought about by MW seem to be counterbalanced by evident costs for cognitive performance (Mooneyham & Schooler, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although these results seem to suggest a straightforward association between creative idea generation and mind wandering, other studies suggest that this relationship is not present in all contexts. Researchers failed to find a relationship between task-unrelated thought and incubation in two conceptual replications (Smeekens & Kane, 2016; Steindorf et al, 2021) and one direct replication (Murray et al, 2021) of Baird et al (2011). Furthermore, Hao et al (2015) found that task-unrelated thought interferes with creative idea generation, when participants go off-task while they are trying to generate creative ideas.…”
mentioning
confidence: 99%
“…The nonidentity of task-unrelated and freely moving thought matters because philosophical (Irving, 2016, 2021) and theoretical (Christoff et al, 2016; Sripada, 2018) models suggest that freely moving thought in particular––rather than task-unrelated thought in general––should facilitate creative-idea generation. Furthermore, researchers who found no benefits of task-unrelated thought during incubation have explicitly hypothesized that freely moving thought may be more helpful (Murray et al, 2021). There are therefore theoretical and empirical reasons to investigate the relationship between freely moving thought and creative idea generation.…”
mentioning
confidence: 99%
See 1 more Smart Citation